Plant resources of South-East Asia: No.7 - Bamboos (Backhuys, 1995)
This book deals with the bamboos of South-East Asia. For centuries bamboos have been of great importance in rural communities in tropical Asia, being used intensively as a sustainable resource for numerous purposes. Bamboos are often classified as minor or non-timber forest products and their value or potential value has been largely underestimated. In recent years the commercialization of bamboo exploitation for commodities such as bamboo shoots, bamboo boards, chopsticks, pulp for paper manufacture, and bamboo handicrafts, has caused an increase in the demand for the raw material. This necessitates sustainable management of natural stands and the establishment of bamboo plantations. Reliable and up-to-data information, however, is scarce. In this book, 45 major bamboo species are highlighted extensively and illustrated, and the characteristics of another 30 minor species are given in brief. The introduction deals with general aspects of bamboo and a glossary explains the terms used